Drugs Interfering with Muscarinic Acetylcholine Receptors and Their Effects on Place Navigation - Svoboda, Jan; Popelikova, Anna; Stuchlik, Ales (Frontiers in Psychiatry, 2017)
Muscarinic receptors have been found to regulate many diverse functions, ranging from motivation and feeding to spatial navigation, an important and widely studied type of cognitive behavior. Systemic administration of non-selective antagonists of muscarinic receptors, such as scopolamine or atropine, have been found to have adverse effects on a vast majority of place navigation tasks. However, many of these results may be potentially confounded by disruptions of functions other than spatial learning and memory. Although studies with selective antimuscarinics point to mutually opposite effects of M1 and M2 receptors, their particular contribution to spatial cognition is still poorly understood, partly due to a lack of truly selective agents. Furthermore, constitutive knock-outs do not always support results from selective antagonists. For modeling impaired spatial cognition, the scopolamine-induced amnesia model still maintains some limited validity, but there is an apparent need for more targeted approaches such as local intracerebral administration of antagonists, as well as novel techniques such as optogenetics focused on cholinergic neurons and chemogenetics aimed at cells expressing metabotropic muscarinic receptors.